Pathways towards sustainability: A capacity needs assessment for the implementation of the Colombian Policy for Sustainable Cattle 2022–2050 - Sandoval Yate, Danny Fernando; Triana Ángel, Natalia; Burkart, Stefan (Elsevier, 2024)
Cattle farming is one of the main agricultural activities in Colombia, but its mainly extensive nature generates significant social and environmental impacts, such as land grabbing, agricultural frontier expansion, increased greenhouse gas emissions, and deforestation. To transform cattle systems towards sustainability, the Policy Guidelines for Sustainable Cattle 2022–2050 (LPGBS) were launched in 2022, resulting from conversations between sector institutions and the national government. Although the LPGBS are proposed as the roadmap for cattle farming in the coming decades, their implementation has faced delays and raised doubts among the involved institutions. This research analyzes the current state of the LPGBS to identify difficulties and determine strategies that promote sustainability in cattle systems by building capacities. The research is based on a mixed-methods approach and contains a literature review on the evaluation of public policies in the cattle sector, complemented by 26 key-informant interviews with experts from public and private institutions involved in developing the LPGBS. These interviews provided key perspectives and practical experiences to understand current difficulties in the implementation of the LPGBS and identify the capacities needed to achieve the planned transition to sustainable cattle farming. Results reveal several difficulties in the LPGBS design stage, including institutional weakness, low governmental participation, and lack of trust among stakeholders. However, important progress was made, such as the construction of social, environmental, and productive sustainability criteria, the consolidation of the sustainability approach at the cattle landscape level, and regional participation. The capacities necessary to drive the implementation of the LPGBS include strengthening rural extension programs, access to financing, and the implementation of a traceability system for monitoring and evaluation. These findings highlight the importance of evaluating policies at early stages to provide crucial information for decision-makers and public policy formulators to correct and improve implementation processes.